2017
DOI: 10.3847/1538-3881/153/3/108
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid 1566 Icarus’s Size, Shape, Orbit, and Yarkovsky Drift from Radar Observations

Abstract: Near-Earth asteroid (NEA) 1566 Icarus (a = 1.08 au, e = 0.83, i = 22.8• ) made a close approach to Earth in June 2015 at 22 lunar distances (LD). Its detection during the 1968 approach (16 LD) was the first in the history of asteroid radar astronomy. A subsequent approach in 1996 (40 LD) did not yield radar images. We describe analyses of our 2015 radar observations of Icarus obtained at the Arecibo Observatory and the DSS-14 antenna at Goldstone. These data show that the asteroid is a moderately flattened sph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…For now, it is possible to adapt the weighting scheme to underweight the observations during the 1968 close approach: this was done by the JPL team, not by the Pisa one. By comparing the result of the two groups, and also with the one in Greenberg et al (2017), we can claim that the detection of the Yarkovsky effect is confirmed, even if there is a significant difference between the standard deviations (see Section 7), which is explained by the different weighting scheme.…”
Section: Accepted and Significant Resultsmentioning
confidence: 74%
“…For now, it is possible to adapt the weighting scheme to underweight the observations during the 1968 close approach: this was done by the JPL team, not by the Pisa one. By comparing the result of the two groups, and also with the one in Greenberg et al (2017), we can claim that the detection of the Yarkovsky effect is confirmed, even if there is a significant difference between the standard deviations (see Section 7), which is explained by the different weighting scheme.…”
Section: Accepted and Significant Resultsmentioning
confidence: 74%
“…Icarus has a critical rotational period (2.273 hours) in which the centrifugal force exceeds the self-gravitational force on the equator. Assuming an Itolawa-like bulk density of ∼2000 kg m −3 (Fujiwara et al 2006;Scheeres et al 2010) and a spherical body with a 1440-m diameter (Greenberg et al 2017), the ambient gravitational acceleration is approximately 80 micro-G's at the pole and minus 5 micro-G's at the equator, suggesting that granular materials may be ejected from the equatorial region (around a latitude within 30 • from the equator) via centrifugal acceleration. In contrast, the rotational axis of Icarus nearly aligns to the ecliptic pole (Greenberg et al 2017), meaning that it is roughly perpendicular to the orbital plane with a moderate inclination to the orbital plane (i=22.3 • ).…”
Section: Consideration Of Mass Ejection Around Perihelionmentioning
confidence: 99%
“…MONTE is used for spacecraft navigation and trajectory design. MONTE has also been used for a variety of scientific purposes, including gravity analysis (Verma & Margot 2016) and ephemeris generation (Greenberg et al 2017).…”
Section: Target Asteroidsmentioning
confidence: 99%
“…This nongravitational effect has been shown to affect the semi-major axes of small bodies due to the anisotropic re-emission of absorbed sunlight (e.g., Bottke et al 2006). The change in semi-major axis with time due to Yarkovsky orbital drift, da/dt , was estimated for all target asteroids with the method of Greenberg et al (2017). The values ranged in amplitude between 4 and 50 au/My, which is plausible for kilometersized bodies.…”
Section: Dynamical Modelmentioning
confidence: 99%